New protein–protein interactions of mitochondrial connexin 43 in mouse heart - Denuc, Amanda (J Cell Mol Med, 2016)
Connexin 43 (Cx43), the gap junction protein involved in cell‐to‐cell coupling in the heart, is also present in the subsarcolemmal fraction of cardiomyocyte mitochondria. It has been described to regulate mitochondrial potassium influx and respiration and to be important for ischaemic preconditioning protection, although the molecular effectors involved are not fully characterized. In this study, we looked for potential partners of mitochondrial Cx43 in an attempt to identify new molecular pathways for cardioprotection. Mass spectrometry analysis of native immunoprecipitated mitochondrial extracts showed that Cx43 interacts with several proteins related with mitochondrial function and metabolism. Among them, we selected for further analysis only those present in the subsarcolemmal mitochondrial fraction and known to be related with the respiratory chain. Apoptosis‐inducing factor (AIF) and the beta‐subunit of the electron‐transfer protein (ETFB), two proteins unrelated to date with Cx43, fulfilled these conditions, and their interaction with Cx43 was proven by direct and reverse co‐immunoprecipitation. Furthermore, a previously unknown molecular interaction between AIF and ETFB was established, and protein content and sub‐cellular localization appeared to be independent from the presence of Cx43. Our results identify new protein–protein interactions between AIF‐Cx43, ETFB‐Cx43 and AIF‐ETFB as possible players in the regulation of the mitochondrial redox state.